The King in his beauty : a Biblical theology of the Old and New Testaments - Schreiner, Thomas R. (Grand Rapids, Michigan : Baker Academic, 2013)
"Thomas Schreiner, a respected scholar and a trusted voice for many students and pastors, offers a substantial and accessibly written overview of the whole Bible. He traces the storyline of the scriptures from the standpoint of biblical theology, examining the overarching message that is conveyed throughout. Schreiner emphasizes three interrelated and unified themes that stand out in the biblical narrative: God as Lord, human beings as those who are made in God's image, and the land or place in which God's rule is exercised. The goal of God's kingdom is to see the king in his beauty and to be enraptured in his glory" -- Publisher description.
Creation to the edge of Canaan -- The story of possession, exile, and return -- Israel's songs and wisdom -- Judgment and salvation in the prophets -- The kingdom in Matthew, Mark, and Luke-Acts -- Eternal life in the Gospel and Epistles of John -- The end of the ages has come accoring to the Apostle Paul -- Living in the last days according to the General Epistles -- The kingdom will come.
Includes bibliographical references (pages 647-662) and indexes.
Keywords: Bible -- Theology; Bible -- Criticism, interpretation, etc; Bible; Theology; Criticism, interpretation, etc